2010
DOI: 10.1021/bi100468v
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Morphology of Self-Assembly of an Elastin-like Polypeptide Based on the Alternating Domain Arrangement of Human Tropoelastin

Abstract: Elastin is the polymeric extracellular matrix protein responsible for the properties of extensibility and elastic recoil in tissues such as arterial blood vessels, lung parenchyma, and skin. Both tropoelastin (TE), the full-length monomeric form of elastin, and elastin-like polypeptides (ELPs), based on sequences and domain arrangements of TE, have the intrinsic ability to undergo organized self-assembly into network structures through a process of temperature-induced phase separation or coacervation. It has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 57 publications
1
67
0
Order By: Relevance
“…Although both of these polypeptides exhibited the presence of ␤-structure as dried monomers as well as in the aggregated state, given the disruptive nature of prolines against ␤-sheet formation, it is probable that domain P6N permits a more extended ␤-structure motif than domain P12. Moreover, the introduction of greater spacing between proline residues correlated with the progressive retardation of droplet growth, consistent with more rapid loss of surface fluidity and stabilization of droplet surfaces, preventing coalescence (30,34). Growing evidence shows that water-hydrophobic interfaces promote the self-organization of amphipathic sequences into ␤-sheet structures (53)(54)(55).…”
Section: Proline Prevents the Aggregation Of Exposed Hydrophobicmentioning
confidence: 76%
See 1 more Smart Citation
“…Although both of these polypeptides exhibited the presence of ␤-structure as dried monomers as well as in the aggregated state, given the disruptive nature of prolines against ␤-sheet formation, it is probable that domain P6N permits a more extended ␤-structure motif than domain P12. Moreover, the introduction of greater spacing between proline residues correlated with the progressive retardation of droplet growth, consistent with more rapid loss of surface fluidity and stabilization of droplet surfaces, preventing coalescence (30,34). Growing evidence shows that water-hydrophobic interfaces promote the self-organization of amphipathic sequences into ␤-sheet structures (53)(54)(55).…”
Section: Proline Prevents the Aggregation Of Exposed Hydrophobicmentioning
confidence: 76%
“…Droplets typically grow (mature) by coalescence before attaining a stable final diameter. The stabilized droplet size is highly dependent on the protein sequence and concentration and on the solvent environment, including the presence of other extracellular matrix proteins (30,34). In this study, the effect of proline spacing on the growth and aggregation characteristics of coacervate droplets was monitored in real time by light microscopy.…”
Section: Distribution Of Proline Residues In Hydrophobic Sequencesmentioning
confidence: 99%
“…We and others have previously shown that colloidal droplets in suspensions held above the coacervation temperature undergo a maturation process involving growth by coalescence and/or clustering (21,29,56,57). We therefore used light microscopy to compare maturation morphologies of the coacervate droplets formed by these three polypeptides.…”
Section: Mutant Elastin-like Polypeptides Have Multiple Possiblementioning
confidence: 99%
“…Coacervation Temperature Correlates with Hydrophobicity and ␤-Sheet Propensity-In general, the coacervation temperature of elastin-like polypeptides has been shown to decrease with increased concentration and molecular weight, as well as with increased solution ionic strength (19,45,57). This phase separation can also be promoted by the addition of relatively low concentrations of TFE to the solution (17).…”
Section: Mutant Elastin-like Polypeptides Have Multiple Possiblementioning
confidence: 99%
“…This self-assembly property of full-length tropoelastin can also be mimicked by smaller polypeptides. Elastin-like polypeptides (ELPs) have the ability to undergo organized self-assembly into network structures through a process of temperature-induced phase separation or coacervation (20) . Elastin-like polypeptides are derived from a repeating motif within a hydrophobic domain of mammalian tropoelastin: the most common motif has the sequence (VPGXG) m , where X can be any amino acid other than proline, and m is the number of repeats (1).…”
Section: Genetically Engineered Polypeptides In Hard Tissue Engineeringmentioning
confidence: 99%